2004
DOI: 10.1542/peds.2004-0803
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Newborn Thyroid Scintigraphy With Isotopic Iodide (123I) in Defining and Managing Congenital Hypothyroidism

Abstract: ABSTRACT. Background. Thyroid imaging with isotopic iodide ( 123 I) or technetium Tc 99m pertechnetate has been available for decades but is not routinely used in newborn infants diagnosed with congenital hypothyroidism (CH). Among clinicians who believe that presence, absence, or abnormal location of a thyroid does not alter management of CH, imaging is not advocated for anatomic diagnosis of CH.Objective. To define the role of thyroid scintigraphy in diagnosing and managing newborn CH.Methods. Results. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 20 publications
5
54
0
7
Order By: Relevance
“…One clue may come from the study of Schoen et al, 6 who evaluated the role of thyroid scintigraphy in diagnosing and managing CH in the newborn period. In a population of Ͼ700 000 newborns in California, there were 249 newborns with a confirmed case of CH, of which 210 received neonatal thyroid scintigraphy to determine the presence, absence, or abnormal location of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One clue may come from the study of Schoen et al, 6 who evaluated the role of thyroid scintigraphy in diagnosing and managing CH in the newborn period. In a population of Ͼ700 000 newborns in California, there were 249 newborns with a confirmed case of CH, of which 210 received neonatal thyroid scintigraphy to determine the presence, absence, or abnormal location of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of most congenital defects of thyroid location or structure are not known, but multiple epidemiologic studies have revealed several consistent trends in associated factors, particularly the newborn's race, ethnicity, sex, birth weight, and gestational age. CH has been reported as more common among Hispanic [4][5][6] and Asian and Native Hawaiian or other Pacific Islander (ANHOPI) 4,5,7 newborns and less common among non-Hispanic black newborns than among non-Hispanic white newborns. 4,5,8 CH occurs more often in girls than in boys, generally with a ratio of 2.…”
mentioning
confidence: 99%
“…Untreated congenital hypothyroidism is one of the most common preventable causes of mental retardation (24). Causes of neonatal hypothyroidism include thyroid agenesis, dysgenesis, or ectopia (25); dyshormonogenesis due to inborn errors in thyroid hormone synthesis (26,27); and transient infantile hypothyroidism caused by maternal thyroid-blocking antibodies, maternal antithyroid medications, or iodine exposure (28). In North America, congenital hypothyroidism has an incidence of approximately 1 in every 3,000-4,000 births, with approximately a 2:1 female predominance (24,27).…”
Section: Thyroidmentioning
confidence: 99%
“…Causes of neonatal hypothyroidism include thyroid agenesis, dysgenesis, or ectopia (25); dyshormonogenesis due to inborn errors in thyroid hormone synthesis (26,27); and transient infantile hypothyroidism caused by maternal thyroid-blocking antibodies, maternal antithyroid medications, or iodine exposure (28). In North America, congenital hypothyroidism has an incidence of approximately 1 in every 3,000-4,000 births, with approximately a 2:1 female predominance (24,27). Nearly all new cases of infantile hypothyroidism in North America and Europe are now detected by neonatal laboratory screening for hypothyroidism, which facilitates prompt evaluation and early institution of thyroid hormone replacement therapy to prevent neurocognitive damage.…”
Section: Thyroidmentioning
confidence: 99%
“…Several imaging studies including thyroid ultrasonography and thyroid scan can determine the underlying causes of hypothyroidism and we can expect the natural course of the thyroid function [5,22]. In addition, it can permit parents to be counseled on either the certainty of lifetime therapy.…”
Section: Discussionmentioning
confidence: 99%